1985
DOI: 10.1128/jcm.22.1.1-4.1985
|View full text |Cite
|
Sign up to set email alerts
|

Second serogroup of Legionella feeleii strains isolated from humans

Abstract: Three strains of Legionellafeeleii from patients with pneumonia (425-MI-H, 691-WI-H, and 693-WI-H) and one environmental strain (713-MI-E) received at the Centers for Disease Control for reference diagnostic testing were compared with the type strain WO-44C-C3 (ATCC 35072) by DNA hybridization, chemical analysis of cellular fatty acids and ubiquinones, biochemical tests, and serological characteristics. All four isolates were assigned to the L. feeleii species on the basis of DNA hybridization results. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…One such candidate for Pontiac fever is L. feeleii, which is aproteolytic (22). In addition, L. micdadei, which is also aproteolytic, produces disease most frequently in immunocompromised hosts (18,26).…”
Section: Discussionmentioning
confidence: 99%
“…One such candidate for Pontiac fever is L. feeleii, which is aproteolytic (22). In addition, L. micdadei, which is also aproteolytic, produces disease most frequently in immunocompromised hosts (18,26).…”
Section: Discussionmentioning
confidence: 99%
“…logical techniques. This practice has led to the identification and description of serologically distinct strains of the same species (Bibb et al 1981;Tang et al 1984;Thacker et al 1985;WiIkinson et al 1985;Benson et al 1988). Strain ML76 was isolated from an environmental source and presumptively identified as a legionella by its nutritional requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Although definitive identification of legionellas can be made only by DNA/DNA homology studies, most newly isolated strains are presumptively identified by nutritional, biochemical and, particularly, serological characteristics. Serological diversity is frequently seen within species, however, and at present L. pneumophila comprises 14 serogroups (Benson et al 1988), and L. bozemanii, L. feeleii, L. hackeliae and L. longbeachae each comprise two serogroups (Bibb et al 1981;Tang et al 1984;Thacker et al 1985;Wilkinson et al 1985).…”
mentioning
confidence: 99%
“…The first case of L. gormanii infection in humans was 0 DFA poly E3 DFA Lp reported in 1988 (7), and that of L. feeleii was reported in 1985 (17,21). That both of these organisms are potentially pathogenic is not in dispute.…”
Section: Resultsmentioning
confidence: 99%